The psychology of group perception : perceived variability, entitativity, and essentialism - Yzerbyt, Vincent; Judd, Charles M.; Corneille, Olivier (Psychology Press, 2004)
This groundbreaking work by leading social psychologists, who have all contributed in important ways to the psychology of group perception, focuses in particular on three interrelated issues: (1) whether groups are seen to be diverse or relatively homogeneous; (2) whether groups are seen as real and stable or only transitory and ephemeral; and (3) whether group membership derives from some essential quality of the members or rather is based on social constructions.